Anticoagulation and bleeding risk in patients with COVID-19. Issue 196 (December 2020) - Musoke, Nancy; Lo, Kevin Bryan; Albano, Jeri; Peterson, Eric; Bhargav, Ruchika; Gul, Fahad; DeJoy, Robert; Salacup, Grace; Pelayo, Jerald; Tipparaju, Padmavathi; Azmaiparashvili, Zurab; Patarroyo-Aponte, Gabriel; et al.
Abstract: Background: There is no current standardized approach to anticoagulation in patients with Coronavirus Disease 2019 (COVID-19) while potential bleeding risks remain. Our study characterizes the patterns of anticoagulation use in COVID-19 patients and the risk of related bleeding. Methods: This is a single center retrospective analysis of 355 adult patients with confirmed diagnosis of COVID-19 from March 1 to May 31, 2020. Chi-square was used to analyze the relationship between degree of anticoagulant dose and bleeding events by site. Multivariable logistic regression was used to look at factors associated with inpatient death. Results: 61% of patients were being treated with prophylactic doses of anticoagulation, while 7% and 29% were being treated with sub-therapeutic and therapeutic anticoagulation (TA) doses respectively. In 44% of patients, we found that the decision to escalate the dose of anticoagulation was based on laboratory values characterizing the severity of COVID-19 such as rising D-dimer levels. There were significantly higher rates of bleeding from non-CNS/non-GI sites (p = 0.039) and from any bleeding site overall (p = 0.019) with TA. TA was associated with significantly higher rates of inpatient death (41.6% vs 15.3% p < 0.0001) compared to those without. All patients who developed CNS hemorrhage died p = 0.011. After multivariable logistic regression, only age OR 1.04 95% CI (1.01 to 1.07) p = 0.008 and therapeutic anticoagulation was associated with inpatient mortality OR 6.16 95% CI (2.96 to 12.83) p ≤ 0.0001. Conclusion: The use of TA was significantly associated with increased risk of bleeding. Bleeding in turn exhibited trends towards higher inpatient death among patients with COVID-19. These findings should be interpreted with caution and larger more controlled studies are needed to verify the net effects of anticoagulation in patients with COVID-19. Highlights: Major bleeding is associated with use of therapeutic anticoagulation in COVID-19. Therapeutic anticoagulation has shown higher mortality and major bleeding trends. Risks and benefits of anticoagulation in COVID-19 should be weighed cautiously.